EFFICACY AND SAFETY OF ENZYME REPLACEMENT THERAPY IN CHILDREN WITH MUCOPOLYSACCHARIDOSIS TYPE I, II, AND VI: A SINGLE-CENTER COHORT STUDY - Liliia A. Osipova; Ludmila M. Kuzenkova; Leyla S. Namazova-Baranova; Anait K. Gevorkyan; Tatiana V. Podkletnova; Nikolay A. Mayanskiy; Grigoriy V. Revunenkov; Nato D. Vashakmadze (Вопросы современной педиатрии, 2018)
Background. There are limited data on the efficacy of long-term enzyme replacement therapy (ERT) in children with mucopolysaccharidosis (MPS).Objective. Our aim was to study the efficacy and safety of long-term ERT in children with MPS type I, II, and VI.Methods. We analyzed the results of ERT with laronidase, idursulfase, and galsulfase in children with MPS type I, II, and VI admitted to the federal research center from January 2007 to November 2016. The response rate was assessed by the level of normalized urinary excretion of glycosaminoglycans (GAGs) (the ratio of GAGs concentration to urine creatinine) recalculated in percent (%) exceedance of the upper limit of normal for the corresponding age. Data on the administered therapy and its results, including adverse events, is extracted from the medical records of in-patients.Results. The results of treatment (intravenous infusions, intervals between administrations from 4 to 10 days) were studied in 33 children (5 of them were girls) with MPS type I (n = 4; laronidase at a dose of 0.58 mg/kg), II (n = 26; idursulfase at a dose of 0.5 mg/kg), and VI (n = 3; galsulfase at a dose of 1 mg/kg). A decrease in the normalized urinary excretion of GAGs from 376% (172; 791) to 54% (0; 146) exceedance of the upper limit of normal for the age (p < 0.001) was noted in the course of ERT lasting (median) 27 (14; 41) months. A decrease in the normalized GAGs excretion below the upper limit of normal for the age was established in 12/33 (36%) patients. ERT-associated adverse events were identified in 12 patients; one case required a two-fold therapy interruption. The development of nephrotic syndrome in the course of ERT in patients with severe MPS II was first described.Conclusion. Long-term ERT in children with MPS type I, II, and VI is characterized by acceptable efficacy and safety. Key words: children, mucopolysaccharidosis, enzyme replacement therapy, laronidase, idursulfase, galsulfase, glycosaminoglycans.